Asychronous Distance Learning System (ADLS) / Lai Guan Siong - Lai , Guan Siong (2004)
Asynchronous Distance Learning System or ADLS for acronym is a web-based system that provides an asynchronous e-learning between the users which, the learning media can be accessed at any time and any way and each individual can set the pace of their own learning A few types of services; such as the forum. Bulletin board and mail are prepare for ADLS to become the system more effective and efficiency. Asynchronous Distance Learning System will be implemented in both Intranet and Internet environment. The main purpose of Asynchronous Distance Learning System development is to implement a computerized learning system to substitute the current traditional In-Class Course Management System. In addition, a few types of new features will enhance within in this system that the users can involved themselves easy, convenience and flexible in the learning system. Asynchronous Distance Learning System consists of three main modules, which are the Administrator Module, Lecturer Module, and the Student Module. The Administrator Module provides system administrator with full authorization to access the database and the whole system. The Lecturer Module provides the functions for editing notes, tutorials and quiz by lecturers. Student Module provides students to access the learning system and other features such as e-mail, notices and forum are prepared for all module to support the ADLS. The benefits of using this system to substitute the current system are to enable better management and speed up the learning processes. Asynchronous Distance Learning System also able to increase the effective and efficiency of current traditional In-Class Course Management System.